Drug encapsulating polysaccharide‐loaded metal nanoparticles: A perspective drug delivery system. Issue 2 (2nd November 2020) - Prasher, Parteek; Sharma, Mousmee; Singh, Samarth Pratap
Abstract: The anticancer and antimicrobial drugs customarily suffer a functional inefficacy due to a limited delivery to the target site, active cellular efflux, in addition to the inadequacy of carrier system. Metal nanoparticles possess unique physicochemical properties as drug delivery vehicles, for delivering the drugs susceptible to cellular efflux pumps. However, a direct physiological exposure of nanoparticle surface after releasing the carrier drug poses serious concerns. The polysaccharides with enhanced biotolerance used for encapsulating the cargo drug molecules, when loaded on the nanoparticle surface presents a perspective drug delivery system combining the physiological benevolence of the former and theranostic/efflux pump evading features of the latter. The present commentary highlight the importance of metal nanoparticle‐loaded polysaccharides as perspective drug delivery system.